Efficacy of Topical Cyclosporine 0.05% the Treatment of Vernal Keratoconjunctivitis - Subedi, Kumudini; Sharma, Binita; Shrestha, Sabina (Nepalese Journal of Ophthalmology, 2020)
Introduction: Vernal Keratoconjunctivitis is a chronic bilateral seasonally exacerbated allergy affecting the conjunctiva and cornea of children. As technology has advanced, newer medications have been developed for the control of the disease.Purpose: To assess the effectiveness of an immunomodulator, cyclosporine, in the treatment of vernal keratoconjunctivitis.Materials and methods: Fifty patients of moderate, severe to very severe vernal keratoconjunctivitis were selected for the study. They were given cyclosporine 0.05% eye drops in loading dose followed by gradual tapering. Symptoms and signs were recorded at presentation, after two weeks, after four weeks, after two months and after three months.Results: Vernal keratoconjunctivitis, being a chronic disease showed marked improvement with immunomodulator therapy. There was significant improvement in the symptom and sign score initially, at the first follow up itself with symptom score reduction from median of mean of 2.4 to 0.6 (p=0.00) and a similar sign score reduction from 1.75 to 0.625 (p=0.00). There was gradually more improvement as therapy continued and the beneficial effects were maintained till the end point of the study at three months where median of mean symptom score was 0.4 (p=0.00) and similar sign score of 0.375 (p= 0.000).Conclusion: Topical cyclosporine proved to be an effective and safe treatment strategy to treat cases of moderate, severe and very severe vernal keratoconjunctivitis.